The Colour Magnitude Diagram of The Galactic Cluster NGC 6383 - Pik Sin The (Institute for Research and Community Services (LPPM) ITB, 1965)
Abstract. Almost all the stars in a circular area with a radius of about 12 min. of arc, were measured photometrically down to V=